2009
DOI: 10.1002/ejic.200801218
|View full text |Cite
|
Sign up to set email alerts
|

A Chloro‐Bridged Linear Chain Imine‐Copper(II) Complex and Its Application as an Enzyme‐Free Amperometric Biosensor for Hydrogen Peroxide

Abstract: The synthesis, structural characterisation and magnetic properties of a new chloro‐bridged linear chain imine‐copper(II) compound are reported. The results indicate that uniform chains are formed by stacking of parallel pyramidal units formed from the copper centre coordinated to the imine ligands and bridged by chloride ions, with the uncoordinated perchlorate ions located between the layers to balance the charge. Magnetic measurements carried out on a powder sample at temperatures from 1.8 to 290 K and a fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 105 publications
2
13
0
6
Order By: Relevance
“…However, although they show outstanding activity and high specificity and selectivity, they have the drawback that they must work at near physiological conditions and are often expensive and unstable during extended usage, although their active lifetimes can be increased by immobilization on electrode surfaces via entrapment, chemical bonding, and cross-linking [15][16][17]. However, these limitations have led to extensive efforts to the synthesis of enzymeless biosensors with a center that is like the three-dimensional catalytic active site of the enzymes [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, although they show outstanding activity and high specificity and selectivity, they have the drawback that they must work at near physiological conditions and are often expensive and unstable during extended usage, although their active lifetimes can be increased by immobilization on electrode surfaces via entrapment, chemical bonding, and cross-linking [15][16][17]. However, these limitations have led to extensive efforts to the synthesis of enzymeless biosensors with a center that is like the three-dimensional catalytic active site of the enzymes [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[45] In contrast, chloride ion has a strong capacity to coordinate metal cations. [70][71][72][73] We therefore concluded that a hydrogen-bonding system consisting of perchlorate anions, hydroxide ions, and the protonated amino groups is most likely present in the form of ÀOH···X À ··· + H 3 NÀ. TG analysis showed that the amount of water confined in the channels was strongly dependent on the counteranion of the copper salt and the surface hydrophobicity ( Figure 5 and Figure S5 in the Supporting Information).…”
mentioning
confidence: 96%
“…Among the new type of electrochemical sensor based on CPs, which was rarely reported, [Cu 2 (tyr) 2 (bipy)] n -CPE showed performance similar to that of [Cu(tyr) 2 ] n /GCE [11] and linear detection range wider than that of GC/PVI/[Cu(2pymehist)Cl](ClO 4 ) [5]. …”
Section: Electrochemical Propertiesmentioning
confidence: 68%
“…However, researches on the electrochemistry of CPs are rare, still less those on CPs' application in electrochemical sensing. In some of these cases, CPs just acted as supporters [3], while in others, they showed inherent electro activity [4,5]. Considering the redox activity of metal elements and/or ligands, and good electric conductivity and nanostructures that CPs may have, we think that proper designed CPs may show good electrochemical properties.…”
Section: Introductionmentioning
confidence: 96%